If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 5 = 53 + -2x Reorder the terms: 5 + 10x = 53 + -2x Solving 5 + 10x = 53 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 5 + 10x + 2x = 53 + -2x + 2x Combine like terms: 10x + 2x = 12x 5 + 12x = 53 + -2x + 2x Combine like terms: -2x + 2x = 0 5 + 12x = 53 + 0 5 + 12x = 53 Add '-5' to each side of the equation. 5 + -5 + 12x = 53 + -5 Combine like terms: 5 + -5 = 0 0 + 12x = 53 + -5 12x = 53 + -5 Combine like terms: 53 + -5 = 48 12x = 48 Divide each side by '12'. x = 4 Simplifying x = 4
| 8(5x-7)=264 | | 23X-4+35X+10=180 | | 5(6x-5)=305 | | 5x+10(25-x)=210 | | 6cd^2+30c^2= | | 10(5x-14)=110 | | x=1.125+1.25y | | 11x+4=9+12x | | -10y+8x=9 | | 1x^4-7x^3+11x^2-5x=0 | | dy/dx=1/2nu | | s-14=24 | | 8x-10y=9 | | 52=66-p | | 54=62-z | | k-45=22 | | 25/4=75/m | | (x+2)(.75)=27 | | 35=50-n | | 43=w-22 | | 2a+2a-a-a+3a= | | 9.8x^2-10x-50=0 | | 29-4x=8-7x | | 32=h-5 | | 93-k=20 | | ln(2x+1)=(x-4) | | 31=b-16 | | 17=61-a | | j-51=21 | | x+1+2x=5x+3 | | 79=97-r | | 48=76-n |